Negotiation : communication for diverse settings - Spangle, Michael (SAGE Publications, 2002)
Negotiation is not formulaic. How we negotiate is determined largely by the context in which the negotiation process takes place. Negotiation: Communication for Diverse Settings provides the reader with a comprehensive overview of the negotiation process as it applies to a wide variety of contexts. Skillfully weaving practitioner interviews and real world examples throughout the book, Michael Spangle and Myra Warren Isenhart emphasize the day-to-day relevance of negotiation skill. The authors provide knowledge vital to successful negotiation in a variety of situations, including interpersonal.